2011
DOI: 10.1007/s11837-011-0180-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of filler-network heterogeneity on thermal resistance of polymeric thermal bondlines

Abstract: How would you……describe the overall significance of this paper? Insight is provided on how to fabricate thermal bondlines so as to maximize thermal conductance, by manipulating filler particles arrangements. Thermal bondlines provide thermal links between heat generating components and heat sinks.…describe this work to a materials science and engineering professional with no experience in your technical specialty? Although it is recognized that the thermal resistance of a thermal bondline is not a material pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The modelling results were found to match the experimental data within 14.3% when the applied pressure was 0.1 MPa. [100,128], geometry [145,146], orientation to the thermal gradient [145,[147][148][149], distribution [127,[150][151][152], and interfacial properties [100,128]. Much literature exists regarding the kTIM models of composites.…”
Section: Thermal Resistance Of Thermal Interface Materials (Tim) and Imentioning
confidence: 99%
See 1 more Smart Citation
“…The modelling results were found to match the experimental data within 14.3% when the applied pressure was 0.1 MPa. [100,128], geometry [145,146], orientation to the thermal gradient [145,[147][148][149], distribution [127,[150][151][152], and interfacial properties [100,128]. Much literature exists regarding the kTIM models of composites.…”
Section: Thermal Resistance Of Thermal Interface Materials (Tim) and Imentioning
confidence: 99%
“…Through multi-modal particle mixing, the smaller particles can fill the gaps between the bigger particles and matrix, forming the preferential paths for heat conduction. Rae et al [152] found that thermal conductivity of the heterogeneous composites can be greater than that of composites filled with homogeneously distributed particles. The heterogeneity of composites in that work was driven by squeeze flow during which filler particles become entrapped and compacted, while the polymer matrix continues to flow.…”
Section: Thermal Resistance Of Tim Controlmentioning
confidence: 99%
“…However, this unique control of microstructure and property for polymer-based composites has less been achieved in practice due to the technical difficulties in controlling the fillers positions. Squeezing [11][12][13] is a process which can make fillers entrapped and compacted in matrix. The heterogeneity of composites occurs when the rate of matrix flow through the fillers is greater than that of composites deformation [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Squeezing [11][12][13] is a process which can make fillers entrapped and compacted in matrix. The heterogeneity of composites occurs when the rate of matrix flow through the fillers is greater than that of composites deformation [12][13]. However, this method is limited to the thin films and demands highly accurate control of the squeeze rate [12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation